2022
DOI: 10.1371/journal.pone.0270997
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of acquiring melioidosis from the environment in the continental United States

Abstract: Melioidosis is an underreported human disease of tropical and sub-tropical regions caused by the saprophyte Burkholderia pseudomallei. Although most global melioidosis cases are reported from tropical regions in Southeast Asia and northern Australia, there are multiple occurrences from sub-tropical regions, including the United States (U.S.). Most melioidosis cases reported from the continental U.S. are the result of acquiring the disease during travel to endemic regions or from contaminated imported materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, it is likely that melioidosis is severely underreported in the 45 countries in which it is endemic and is likely be endemic in a further 34 countries [3] . Indeed, a recent CDC Health Advisory (July 2022) has indicated that melioidosis is also endemic in areas of the Mississippi Gulf Coast and persists in the environment in Texas [4] . It is the most common cause of community-acquired bacteraemia and the third most common cause of death from infectious disease in Thailand [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is likely that melioidosis is severely underreported in the 45 countries in which it is endemic and is likely be endemic in a further 34 countries [3] . Indeed, a recent CDC Health Advisory (July 2022) has indicated that melioidosis is also endemic in areas of the Mississippi Gulf Coast and persists in the environment in Texas [4] . It is the most common cause of community-acquired bacteraemia and the third most common cause of death from infectious disease in Thailand [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of B. thailandensis in the environment in the Western Hemisphere remains poorly understood. We used a systematic approach to detect and isolate B. thailandensis from soil and water samples collected in Texas in November 2019 and November 2020 ( 9 ) and Puerto Rico during December 2018–March 2020.…”
mentioning
confidence: 99%
“…pseudomallei . Establishment of the disease in this environment that favors the survival of the pathogen should be seriously considered as a public health threat for the residents of the Gulf coast region [ 8 ].…”
mentioning
confidence: 99%
“…However, in recent years, the presence of B. pseudomallei has been demonstrated in the African and American continents and in the Caribbean islands as well as the rest of Asia [3][4][5][6]. The continental United States had never confirmed an endemic case of the disease and it was presumed that all the melioidosis patients from the continental US acquired the disease while traveling to endemic areas around the globe [7,8]. In fact, melioidosis was considered a traveler's disease because incidence in the continental US was associated with international acquisition [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation